3D composite reinforcement meso F.E. analyses based on X-ray computed tomography. (15th November 2015) - Naouar, N.; Vidal-Salle, E.; Schneider, J.; Maire, E.; Boisse, P.
Abstract: Meso-FE modelling of 3D textile composites is a powerful tool, which can help determine mechanical properties and permeability of the reinforcements or composites. The quality of the meso FE analyses depends on the quality of the initial model. A direct method based on X-ray tomography imaging is introduced to determine finite element models based on the real geometry of 3D composite reinforcements. The method is particularly suitable regarding 3D textile reinforcements for which internal geometries are numerous and complex. The approach used for the separation of the yarns in different directions is specialised because the fibres flow in three-dimensional space. An analysis of the image's texture is performed. The homogeneity parameter has proved to be the most efficient criterion to separate the yarns numerically. A hyperelastic model developed for fibre bundles is used for the simulation of the deformation of the 3D reinforcement. Meso-FE simulations based on this approach are performed in the event of transverse compaction of a 3D orthogonal reinforcement. The deformation of the yarns' geometry in the simulation is compared with real conditions.